2020
DOI: 10.3390/ph13110334
|View full text |Cite
|
Sign up to set email alerts
|

Toxicokinetics and Toxicodynamics of Ayahuasca Alkaloids N,N-Dimethyltryptamine (DMT), Harmine, Harmaline and Tetrahydroharmine: Clinical and Forensic Impact

Abstract: Ayahuasca is a hallucinogenic botanical beverage originally used by indigenous Amazonian tribes in religious ceremonies and therapeutic practices. While ethnobotanical surveys still indicate its spiritual and medicinal uses, consumption of ayahuasca has been progressively related with a recreational purpose, particularly in Western societies. The ayahuasca aqueous concoction is typically prepared from the leaves of the N,N-dimethyltryptamine (DMT)-containing Psychotria viridis, and the stem and bark of Baniste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
98
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(104 citation statements)
references
References 211 publications
(436 reference statements)
3
98
0
3
Order By: Relevance
“…No clinical studies of DMT use alone in depression treatment were found, as all of the included studies dosed ayahuasca, and it should be remembered that ayahuasca is administered with monoamine oxidase inhibitors, which may have an effect on mood themselves. It should also be remembered that ayahuasca contains other alkaloids, such as harmine or harmaline, and since it is a decoction of the plants themselves, it is difficult to estimate the dose of alkaloids consumed [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…No clinical studies of DMT use alone in depression treatment were found, as all of the included studies dosed ayahuasca, and it should be remembered that ayahuasca is administered with monoamine oxidase inhibitors, which may have an effect on mood themselves. It should also be remembered that ayahuasca contains other alkaloids, such as harmine or harmaline, and since it is a decoction of the plants themselves, it is difficult to estimate the dose of alkaloids consumed [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It becomes orally active when ingested in the presence of a MAO inhibitor such as β-carbolines. This allows DMT to cross the blood-brain barrier intactly and exert its effect in the central nervous system [14][15][16][17][18][19]. Following the administration of ayahuasca, DMT and β-carboniles are present in the human organism and are metabolized and excreted in the urine [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…DMT is metabolized to the oxidative deamination product 3-indole-acetic acid obtained by the MAO pathway, and to the oxidative product DMT-N-oxide (DMT-NO) mediated by cytochrome P-450. Further N-demethylation produces N-methyltryptamine (NMT), which later turns to 2-methyl-1,2,3,4-tetrahydroβ-carboline (2-MTHBC) [19]. Harmine and harmaline are demetylated into harmol and harmalol and hydroxylized by the CYP450 enzyme complex.…”
Section: Introductionmentioning
confidence: 99%
“…From a pharmacological and chemical point of view, salvinorin A is quite unique due to two main features: (i) it is the only known non-alkaloidal hallucinogen, and (ii) it is the first naturally occurring non-nitrogenous compound that acts as an efficacious and potent κ-opioid receptor (KOP)-selective agonist [8][9][10][11]. Although not having affinity for the 5-HT 2A receptors known to mediate the hallucinogenic properties of the classic psychedelics, such as lysergic acid diethylamide (LSD), psilocybin [12], mescaline [13], and N,N-dimethyltryptamine (DMT) [14], salvinorin A induces similar psychoactive effects, including perceptual distortions, alterations in affect, behaviour, and cognition, and out-ofbody experiences, with such effects being intense and short-lived [3,15]. The consumption of this substance has been associated with minimal or no health risks, thus being conceded as a safe hallucinogen [3].…”
Section: Introductionmentioning
confidence: 99%